2021
DOI: 10.3389/fmicb.2021.716196
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sugarcane Rhizosphere Bacterial Community to Drought Stress

et al.

Abstract: Sugarcane is an important sugar and energy crop, and its yield is greatly affected by drought. Although a large number of studies have shown that rhizosphere microorganisms can help improve the adaptability of plants to biotic or abiotic stresses, there is a lack of studies on the adaptability of sugarcane rhizosphere microbial communities to host plants. Therefore, we conducted drought stress treatment and normal irrigation treatment on three sugarcane varieties GT21, GT31, and GT42 widely cultivated in Guang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
(69 reference statements)
2
9
0
Order By: Relevance
“…Drought and salt stress changed the rhizosphere soil bacterial community structure of Nitraria tangutorum Changes in soil physicochemical properties significantly affect soil bacterial community structure and diversity (Orozco-Aceves et al, 2017;Huang et al, 2019). However, in the present study, there were no significant differences in the abundance and diversity of N. tangutorum rhizosphere soil bacteria under drought and salt stress compared with those in CK, indicating that the rhizosphere bacterial community structure was stable, consistent with the results of Liu et al (2021). NMDS analysis showed that the bacterial community structure of N. tangutorum rhizosphere soil was similar under drought and CK (Figure 2), which might be caused by a single species and limited diffusion of the bacterial community.…”
Section: Discussionsupporting
confidence: 87%
“…Drought and salt stress changed the rhizosphere soil bacterial community structure of Nitraria tangutorum Changes in soil physicochemical properties significantly affect soil bacterial community structure and diversity (Orozco-Aceves et al, 2017;Huang et al, 2019). However, in the present study, there were no significant differences in the abundance and diversity of N. tangutorum rhizosphere soil bacteria under drought and salt stress compared with those in CK, indicating that the rhizosphere bacterial community structure was stable, consistent with the results of Liu et al (2021). NMDS analysis showed that the bacterial community structure of N. tangutorum rhizosphere soil was similar under drought and CK (Figure 2), which might be caused by a single species and limited diffusion of the bacterial community.…”
Section: Discussionsupporting
confidence: 87%
“…Rhizobia species are plant growthpromoting bacteria that provide nitrogen to hosts by binding to plant roots [38]. Rhizobia populations have been previously studied in the soil and roots of sugarcane [20,39]. We also isolated a strain (R1) from the roots of sugarcane under FL that was most closely clustered with Rhizobium, and the phylogenetic tree suggested that this isolate might represent a new species (Figure 5a).…”
Section: Discussionmentioning
confidence: 87%
“…Many previous studies have used various sequencing technologies to study bacterial communities, and these studies have provided key insights into the diverse ways in which microbes can affect plants. For example, Wang et al [20] studied the response of the sugarcane rhizosphere bacterial community to drought stress, Achouak et al [21] examined the control of microbial denitrification activity by plant hosts; and Guyonnet et al [22] found that plant nutrient resource use strategies shape active rhizosphere microbiota through root exudation using metabarcoding sequencing.…”
Section: Of 14mentioning
confidence: 99%
“…Members of Streptomycetales, for instance, are known as important symbiosis modulators by inhibiting growth of pathogenic fungi and promoting ectomycorrhizal growth formation 53 . In crop plant systems, such as soybean roots, rice roots or sugarcane rhizosphere, it has been reported that Burkholderiales, Streptomycetales and Rhizobiales act as plant growth promoting bacteria and are the core-responsive bacteria under drought conditions, mediating drought tolerance [54][55][56] . However there is still a lack of knowledge about the role of non-easily culturable bacteria living in the mycorrhizosphere.…”
Section: Discussionmentioning
confidence: 99%